6-10-14 for Health - as an example of an interdisciplinary model of care for a patient with obesity. (20th October 2021) - Metelska, P; Brzeziński, M; Jankowski, M; Niedzielska, A
Abstract: Issue: Overweight and obesity are public health challenges of growing importance in Poland. The fastest increase has been observed in children and adolescents. Some studies show that 22% of elementary school children are currently (2013) overweight or have obesity (IZZ), compared with no more than 15% in 1990 (WHO Europe, 2012). Description of the problem: The "6-10-14 for Health" is the first comprehensive health programme implemented in Poland, focused on long-term health behaviour change both among children with obesity and their families. Screening tests are carried out at Gdańsk schools. Children who are diagnosed with excess body weight are invited to the second level of programme. Target groups are children in Gdansk, aged 6, 9-11 and 14 years, their parents and the school environment. Timeline: 2011-2021 Results: effects: Approximately 400-450 new patients join the programme every year. Programme participants receive annual care from an interdisciplinary team of specialists including a paediatrician, dietitian, specialist in physical activity and a psychologist. The effect of one year's participation in the programme is the reduction of excess body weight in 75% of participants. More then 2000 patients have complieted the Programme. The programme is accredited by the European Association for the Study of Obesity and is funded by the City of Gdańsk. changes: Further implementation of the Programme depends on providing funds from the City of Gdańsk. However, it seems that the 6-10-14 for Health is one of the city's health priorities. The challenge in the field of weight reduction programs is to provide care that will not lead to stigmatization of patients Lessons: The work on designing the model has already resulted in creation of network of specialists from different backgrounds and allowed sharing different scopes, how to use limited resources for the benefit of children and adolescens. Key messages: The proposed care model is fully possible to implement in the care system. So far, sharing knowledge and experience, the program has been implemented in several other local governments. In the era of the COVID19 pandemic, all activities aimed at the prevention and early treatment of obesity become even more important.